2001
DOI: 10.1046/j.1525-1438.2001.11(suppl.1)sup1021.x
|View full text |Cite
|
Sign up to set email alerts
|

The integration of paclitaxel and new platinum compounds in the treatment of advanced ovarian cancer

Abstract: There has been a steady improvement in the survival of patients with advanced ovarian cancer. This has been the result of a more skilled surgical approach to these patients and the development of more effective chemotherapy with a better integration of both modalities in first-line treatment. The current optimal chemotherapeutic approach consists of a platinum compound together with paclitaxel. This recommendation is based upon level I evidence of two large randomized trials which established that the combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
1
12
0
1
Order By: Relevance
“…Oxaliplatin produces the same type of interand intrastrand crosslinks as cisplatin but DACH--platinum adducts are bulkier and more hydrophobic than cisplatin/ carboplatin adducts. Therefore, oxaliplatin may be more effective in DNA replication impairment and its antitumor activity is only partially cross-resistant with cisplatin and carboplatin [8]. Moreover, in cancer cell lines and in clinical studies, oxaliplatin has demonstrated to be superadditive and/or synergistic with cisplatin and carboplatin [15][16][17][18].…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Oxaliplatin produces the same type of interand intrastrand crosslinks as cisplatin but DACH--platinum adducts are bulkier and more hydrophobic than cisplatin/ carboplatin adducts. Therefore, oxaliplatin may be more effective in DNA replication impairment and its antitumor activity is only partially cross-resistant with cisplatin and carboplatin [8]. Moreover, in cancer cell lines and in clinical studies, oxaliplatin has demonstrated to be superadditive and/or synergistic with cisplatin and carboplatin [15][16][17][18].…”
Section: Chemistrymentioning
confidence: 99%
“…Although its mechanism of action is similar to that of the classic platinum compounds [7], oxaliplatin is only partially cross-resistant with cisplatin and carboplatin and had been demonstrated to be synergistic with these platinum agents in in vitro and in vivo models [8]. Moreover, oxaliplatin is featured by favorable side-effect profile compared to cisplatin and neurotoxicity, usually reversible, and is considered the dose-limiting toxicity [8]. Indeed, oxaliplatin could be considered for the treatment of patients who experienced hypersensitivity reactions to platinum, especially in heavily pretreated population [9].…”
Section: Introductionmentioning
confidence: 99%
“…The pooled response rate for each cohort described was the combined complete and partial response rates of each study based on the published response rate, assuming a standardised measure of response was used in the study. Patients recruited earlier than 1995 were assumed to be taxane naïve as platinum/paclitaxel combination therapy was only adopted as first-line therapy for ovarian cancer after several successful trials in 1996 showed the superiority of this regimen compared to the then standard therapy of cisplatin/cyclophosphamide 17,18 . This group of patients were analysed separately as there is the possibility that this group may have received prior paclitaxel salvage therapy.…”
Section: Literature Searches For Clinical Studiesmentioning
confidence: 99%
“…Severe toxicity included neutropenia (21% of patients), febrile neutropenia (7%), and reversible grade 2 or higher neurosensory toxicity (21%). The oxaliplatin plus paclitaxel combination showed high antitumor activity and safe toxicity profile as a firstline adjuvant treatment for advanced ovarian cancer (46) . If this were confirmed in a large randomized trial, it would be sure that the passion will be reignited to make oxaliplatin the limelight in ovarian cancer treatment.…”
Section: Oxaliplatin Plus Paclitaxelmentioning
confidence: 99%